Human Rights and Economic Systems : Kenya’s Economic Policy and the Realisation of Socio-Economic Rights - Killander, Magnus (University of Pretoria, 2021)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2021.